A neurobiological enquiry into the origins of our experience of the sublime and beautiful - Ishizu, Tomohiro; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
Philosophies of aesthetics have posited that experience of the sublime – commonly but not exclusively derived from scenes of natural grandeur – is distinct from that of beauty and is a counterpoint to it. We wanted to chart the pattern of brain activity which correlates with the declared intensity of experience of the sublime, and to learn whether it differs from the pattern that correlates with the experience of beauty, reported in our previous studies (e.g. Ishizu and Zeki, 2011). 21 subjects participated in a functional magnetic resonance imaging experiment. Prior to the experiment, they viewed pictures of landscapes, which they rated on a scale of 1–5, with 5 being the most sublime and 1 being the least. This allowed us to select, for each subject, five sets of stimuli – from ones experienced as very sublime to those experienced as not at all sublime – which subjects viewed and re-rated in the scanner while their brain activity was imaged. The results revealed a distinctly different pattern of brain activity from that obtained with the experience of beauty, with none of the areas active with the latter experience also active during experience of the sublime. Sublime and beautiful experiences thus appear to engage separate and distinct brain systems.